“RATING”: IS THIS WORD MOBILIZING OR MISLEADING? - Ivan E. Zadorozhnyuk (Высшее образование в России)
Russia enters a postHindustrial stage of social development. It is characterized by an important place of the universities as a key producer and also consumer of modern knowledge. Today Russian universities come in productive competition with foreign universities. The author presents his reflections on the problem of universities rating in connection with the release of the twoHvolume works of the Centre for Sociological Researchof the Ministry of Education and Science of Russian Federation (University Ranking: International and Russian Experience/ F.E.Sheregui, and A.L. Arefiev (Eds) / The Ministry of Education and Science of Russian Federation. Moscow: Centre for Sociological Research Publ., 2014. 504 p.; University Ranking: International and Russian Experience. Issue 2 / G.V. Osipov, and A.L. Arefiev (Eds) / The Ministry of Education and Science of Russian Federation. Moscow: Centre for Sociological Research Publ., 2014. 588 p.